Fiscal storms: Public spending and revenues in the aftermath of natural disasters - Ilan Noy; Aekkanush Nualsri (University of California, Santa Cruz Institute for International Economics (SCIIE), 2008)
Recent research in both the social and natural sciences has been devoted to increasing our ability to predict disasters, prepare for them and mitigate their costs. Curiously, we appear to know very little about the fiscal consequences of disasters. The likely fiscal impact of a natural disaster has not been examined before in any comparable or comparative framework. We estimate and quantify the fiscal consequences of natural disasters using quarterly fiscal and disaster data for a large panel of countries. In our estimations, we employ a panel VAR framework that is similar to Burnside et al. (Journal of Economic Theory, 2004), that also controls for the business cycle. We find fiscal behavior in the aftermath of disasters in developed countries that can best be characterized as counter-cyclical. In contrast, we find pro-cyclical decreased spending and increasing revenues in developing countries following large natural disasters. We quantify these effects.
Keywords: E62; O23; Q54; 330; natural disasters; fiscal policy; Naturkatastrophe; Öffentliche Ausgaben; Öffentliche Einnahmen; Finanzpolitik; Vergleich; Welt